Examining stevenson's conceptualisation of entrepreneurship as opportunity-based firm behaviour and its prevalence in technology-based firms in Malaysia - Abdul Majid, Izaidin; Levie, Jonathan; Cooper, Sarah; Ismail, Kamariah (2009)
Opportunity-based firm behaviour or in this paper is referred as Entrepreneurial Management (EM) as coined by Stevenson (2000) is defined as a process by which individuals, either on their own or inside organisations, pursue opportunities regardless of the resources they currently control. It is interesting to note that this study is conducted within a new business context in an Asian country, Malaysia i.e., Malaysian-owned Multimedia Super Corridor (MSC) status companies. This paper shows how the operationalisation of this approach is replicated in the Malaysian business context. The analysis employed here is the exploratory factor analysis and Cronbach’s Alpha test on the data set. The results show that it was possible to identify five sub-dimensions of the opportunity-based firm behaviour construct with high discriminant validity and moderate to high reliabity, which represent dimensions of Stevenson’s theoretical reasoning. The EM measure has been successfully broken down into five factors or sub-dimensions of EM (short of one sub-dimension compared to the original EM measure) which were maintained and labelled as that of the original measure, i.e. Management Structure, Strategic Orientation, Growth Orientation, Entrepreneurial Culture and Resource Orientation. While the measure does not include Reward Philosophy making it short of one factor from the original EM measure, the clean results obtained from the factor analysis, i.e. the remarkably clear and stable factor pattern, would suffice for claiming that the researcher has managed to arrive at an EM measure that is acceptable to be used in gauging the entrepreneurial propensity of the sample firms. This study helps in terms of extending the measure to other business contexts beyond the US and European business cultures (Brown et al., 2001 on a Swedish sample, and Harm and Ehrmann, 2003 on a German sample), i.e. the Malaysia business culture which is an important validation task that would increase the usefulness of the operationalisation of the EM measure. Results suggest that although the EM constructs was developed and operationalised in the developed countries, the US and Europe, it is also applicable in the science or technology parks business context of the developing countries of Asia, i.e. the MSC of Malaysia. Based on the global measure of EM the results of the descriptive statistical analysis suggest that a large majority of the firms may be classified as entrepreneurial. On further investigation on each dimension of the EM construct, mixed results were found on the prevalence of EM. MS, SO and EC dimensions show high prevalence in firms with strong entrepreneurial propensity.